PENGARUH KONSEP BALANCED SCORECARD TERHADAP KINERJA PT.TASPEN (Persero) CABANG SURAKARTA - Rukmini Rukmini (ITB AAS INDONESIA, 2022)
This study aims to determine the effect of financial perspective, customer perspective, internal business perspective and learning and growth perspective on the performance of PT.TASPEN (Persero) Surakarta Branch. This research uses a quantitative descriptive approach, with a sample of 35 employee respondents and 100 respondents participating in TASPEN. Primary data were obtained from questionnaires filled out by respondents who had tested their validity and reliability. The data analysis technique uses multiple linear regression analysis. The results of this study note that the financial perspective variable has a value of tcount (-2.145) < ttable (-1.679) it means that the financial perspective has a negative and significant effect on the performance of PT.TASPEN (Persero) Surakarta Branch. The customer perspective variable has a value of tcount (2.659)> ttable (1.697) meaning that the customer perspective has a positive and significant effect on the performance of PT.TASPEN (Persero) Surakarta Branch. The internal business process perspective variable has a value of tcount (2.659)> ttable (1.697) it means that the perspective of internal business processes has a positive and significant effect on the performance of PT.TASPEN (Persero) Surakarta Branch. Growth and learning perspective variables have a value of tcount (3.170)> ttable (1.697) it means that the perspective of growth and learning has a positive and significant effect on the performance of PT.TASPEN (Persero) Surakarta Branch. F test results obtained value Fcount> Ftable is 46.305> 2.690 it means that the financial perspective, customer perspective, internal business perspective, learning perspective and growth simultaneously influence the performance of PT.TASPEN (Persero) Surakarta Branch.